The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/jsm.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Sustained Heat Treatment on Delayed-Onset Muscle Soreness

Abstract: Although cold is commonly used after heavy exercise to reduce soreness, heat applied just after exercise seems very effective in reducing soreness. Unlike cold, it increases flexibility of tissue and tissue blood flow. For joint, it is still probably better to use cold to reduce swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 70 publications
0
21
0
2
Order By: Relevance
“…For example, Mayer and coworkers reported that treatment with a heat wrap starting 4 h after a bout of eccentric lumbar extension exercise was more effective at reducing local pain than cryotherapy (24). Petrofsky and coworkers recently showed that a heat wrap placed over the quadriceps immediately after a bout of eccentric exercise significantly reduced perceived pain compared with a control intervention (36). This hypoalgesic effect of HT is thought to be caused in part by heat-induced increases in blood flow (13) and the consequent accelerated removal of factors that sensitize muscle nociceptors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mayer and coworkers reported that treatment with a heat wrap starting 4 h after a bout of eccentric lumbar extension exercise was more effective at reducing local pain than cryotherapy (24). Petrofsky and coworkers recently showed that a heat wrap placed over the quadriceps immediately after a bout of eccentric exercise significantly reduced perceived pain compared with a control intervention (36). This hypoalgesic effect of HT is thought to be caused in part by heat-induced increases in blood flow (13) and the consequent accelerated removal of factors that sensitize muscle nociceptors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, DOMS occurs between 24–48 hr after exercise and eventually induces a reduction in muscle function and range of motion with a concomitant increase in creatine kinase (CK) activity, thus causing psychological discomfort ( Evans et al, 1986 ; Kim and Lee, 2014 ; Serinken et al, 2013 ). Several interventions are recommended for reducing DOMS, including cold-water immersion, heat, manual therapy, vibration therapy, compression garments, and nutritional supplements ( Cochrane, 2017 ; Fonseca et al, 2016 ; Jakeman et al, 2010 ; Kim and Lee, 2014 ; Petrofsky et al, 2017 ; Urakawa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, during the administration of heat therapy, relaxation belts in labor can maintain the vascular system components in a vasodilatation state so that blood circulation to the pelvic muscles becomes homeostatic, which can reduce anxiety and pain during labor. 18 The provision of heat therapy with a temperature of 45 ° C for 60 minutes in the T10, T11, T12, and L1 regions, will signal the hypothalamus stimulated through the spinal cord. The effector system will emit a signal in peripheral vasodilation.…”
Section: Discussionmentioning
confidence: 99%